The Role of Gas3 in Skin Tumorigenesis - Yadollahi, Beta (University of Ottawa (Canada), 2010)
Retinoic acid (RA) plays an integral role during embryonic development, in addition to being a potential chemotherapeutic and chemopreventative agent in various cancer models due to its growth inhibitory and pro-differentiation properties. RA signaling occurs in a ligand-dependent manner through a family of nuclear receptors consisting of the RARs and RXRs. RA elicits growth inhibitory effects in transformed wild type keratinocytes, however the target genes that mediate this outcome remain largely unidentified. In order to isolate genes that could mediate the latter effects, a suppressive subtractive hybridization experiment was conducted by our lab and revealed growth arrest specific 3 (gas3) as a candidate gene. Gas3 is expressed in the skin and is induced by RA as early as two hours post-treatment in tissue culture models. We investigated a possible relationship between gas3 and epidermal tumorigenesis and found that this gene behaves in a context dependent, strain-specific manner as both an RA-mediated tumor suppressor and an oncogene. To further investigate this, I first demonstrated that RA-induced growth arrest in keratinocytes is mediated in part by gas3. Additionally, previous work from our lab demonstrated that gas3-null mice from an FVB/NJ background evaded tumor formation following the two-stage carcinogenesis protocol. I demonstrate that this occurs as a result of an increase in apoptotic response following chemical mutagenesis in gas3 mutants. Conversely, I found that Gas3 mutants on a C57Bl/6 background behave as wild type animals with respect to carcinogenesis, suggesting that genetic modifiers between these two strains impact on Gas3 function with respect to tumorigenesis. Finally, I found that p21 activity is affected by the loss of gas3, which may begin to elucidate how gas3 impacts on carcinogenesis.
Keywords: Biology, Molecular.